Systematic review and consensus definitions for the Standardised Endpoints in Perioperative Medicine initiative: clinical indicators. (August 2019) - Haller, Guy; Bampoe, Sohail; Cook, Tim; Fleisher, Lee A.; Grocott, Michael P.W.; Neuman, Mark; Story, David; Myles, Paul S.; ,
Abstract: Background: Clinical indicators are powerful tools to quantify the safety and quality of patient care. Their validity is often unclear and definitions extremely heterogeneous. As part of the International Standardised Endpoints in Perioperative Medicine (StEP) initiative, this study aimed to derive a set of standardised and valid clinical outcome indicators for use in perioperative clinical trials. Methods: We identified clinical indicators via a systematic review of the anaesthesia and perioperative medicine literature (PubMed/OVID, EMBASE, and Cochrane Library). We performed a three-stage Delphi consensus-gaining process that involved 54 clinician–researchers worldwide. Indicators were first shortlisted and the most suitable definitions for evaluation of quality and safety interventions determined. Indicators were then assessed for validity, reliability, feasibility, and clarity. Results: We identified 167 clinical outcome indicators. Participation in the three Delphi rounds was 100% ( n =13), 68% ( n =54), and 85% ( n = 6), respectively. A final list of eight outcome indicators was generated: surgical site infection at 30 days, stroke within 30 days of surgery, death within 30 days of coronary artery bypass grafting, death within 30 days of surgery, admission to the intensive care unit within 14 days of surgery, readmission to hospital within 30 days of surgery, and length of hospital stay (with or without in-hospital mortality). They were rated by the majority of experts as valid, reliable, easy to use, and clearly defined. Conclusions: These clinical indicators can be confidently used as endpoints in clinical trials measuring quality, safety, and improvement in perioperative care. Registration: PROSPERO 2016 CRD42016042102 (http://www.crd.york.ac.uk/PROSPERO/display_record.php? ID=CRD42016042102).